Management Education in India - Pylee, M. V. (Management Science, 1967)
Fifteen years ago hardly anyone had thought seriously about the need of organized management education in India. Soon after Independence in 1947 a high level Commission on Education was appointed by the Government of India with Dr. S. Radhakrishnan (the present President of India) as Chairman to make a comprehensive study of the various aspects of the educational system then existing and make recommendations for its modification for the new requirements of the nation. This commission however, had little to say on management education. But the formulation of a definite program for planned economic development soon after, brought about a complete change in the situation. The need for technically trained and competent administrative personnel became urgent. As a result, during the past one decade there has been an increasing awareness of the need for providing facilities of training in management.